Age and stand structure of oak woodlands along a gradient of conifer encroachment in northwestern California. Issue 10 (8th October 2018) - Schriver, Madelinn; Sherriff, Rosemary L.; Varner, J. Morgan; Quinn‐Davidson, Lenya; Valachovic, Yana
Abstract: Many fire‐maintained savannas and woodlands are suffering the effects of fire exclusion and the concomitant invasion of fire‐sensitive trees. In the Pacific West, woodlands dominated by either Oregon white oak ( Quercus garryana ) or California black oak ( Quercus kelloggii ) have transitioned from oak‐dominated to conifer‐dominated (primarily by the native Douglas‐fir; Pseudotsuga menziesii ) forest conditions with corresponding losses of plant and animal biodiversity. In spite of the prevalence of this transition, few studies have documented these temporal shifts and the consequences for oak woodland ecosystems. To better understand this process, we assessed tree species composition and age structure across 10 sites in northwestern California, USA. Species composition varied, but Douglas‐fir, Oregon white oak, and California black oak had the greatest proportional dominance within and across sites. Across all ten sites, we cored 1747 trees from 10 different species. The majority (>80%) of oak stems dated between 1850 and 1910 (69% plots dated within a 40‐yr period from 1860 to 1900). Less than 1% of the oak stems originated after 1960. Across the gradient of encroachment (i.e., oak to conifer dominance) at each site, the most common encroaching species was Douglas‐fir, which primarily established after 1970 (73% across all sites). Douglas‐fir structural attributes were not associated with any of the abiotic factors evaluated, although non‐significant trends show greater densities of Douglas‐fir in oak stands at the northern end of the study region. Oak seedlings were common in all 10 study sites; however, we documented very few oak saplings regardless of the biophysical conditions. This study highlights that (1) the process and severity of encroachment is consistent across the region, resulting in substantial oak habitat loss and a shift toward conifer dominance and vegetative homogeneity in formerly diverse woodlands of northwestern California; and (2) Oregon white oak and California black oak woodlands require concerted management effort to ensure their survival and future persistence.